2002
DOI: 10.1111/j.1151-2916.2002.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Microstructure of Silicon Nitride/Boron Nitride Nanocomposites

Abstract: A chemical process for fabrication of Si3N4/BN nanocomposite was devised to improve the mechanical properties. Si3N4/BN nanocomposites containing 0 to 30 vol% hexagonal BN (h‐BN) were successfully fabricated by hot‐pressing α‐Si3N4 powders, on which turbostratic BN (t‐BN) with a disordered layer structure was partly coated. The t‐BN coating on α‐Si3N4 particles was prepared by reducing and heating α‐Si3N4 particles covered with a mixture of boric acid and urea. TEM observations of this nanocomposite revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 35 publications
6
87
1
Order By: Relevance
“…The bending strength was 400-450 MPa, which were the same level as that of the conventional monolithic alumina ceramics while the fracture toughness was 3.7-3.9 MPa·m 0.5 , which were little higher than that of the conventional monolithic alumina ceramics. The Vickers hardness was [11][12][13][14] GPa, which was the same level as that of zirconia ceramics. 9.…”
mentioning
confidence: 62%
“…The bending strength was 400-450 MPa, which were the same level as that of the conventional monolithic alumina ceramics while the fracture toughness was 3.7-3.9 MPa·m 0.5 , which were little higher than that of the conventional monolithic alumina ceramics. The Vickers hardness was [11][12][13][14] GPa, which was the same level as that of zirconia ceramics. 9.…”
mentioning
confidence: 62%
“…8 Among those materials, h-BN, which exhibits high thermal conductivity and high melting point, is regarded as a suitable and effective interface material since the cleavage plane of h-BN facilitates crack propagation and decreases the cutting resistance during machining. [9][10][11][12] Besides these, the similar crystal structures of BN and ZrB 2 ensure the good chemical compatibility between them. Therefore, ZrB 2 -SiC-BN system may be a good candidate material for high temperature ceramics with excellent machinability and mechanical properties.…”
Section: Introductionmentioning
confidence: 97%
“…On the other resistance property and good machinability (Kusunose et al, , 2002a(Kusunose et al, ,b, 2005Niihara, 1991). Niihara and Kusunose reported that they have prepared the Si 3 N 4 /BN nanocomposite powders by the chemical reaction of H 3 BO 3 and CO(NH 2 ) 2 on the surface of Si 3 N 4 particles at high temperature, and the Si 3 N 4 /BN nanocomposites were fabricated by the hot-pressing process (Kusunose et al, , 2002a. They also have fabricated the Al 2 O 3 /BN nanocomposites by the same process (Kusunose et al, 2005).…”
Section: Introductionmentioning
confidence: 99%